The Influence of Website-Based Learning Media on Science Learning Outcomes in Elementary School Students in the Era of Society 5.0 - Rosa Ardiana Ningrum; Wahono Widodo; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2024)
Objective: In the era of global society 5.0, people worldwide are faced with demands to keep pace with the development of technology and knowledge by developing their "hard skills" and "soft skills." Ever-evolving technologies are utilized to achieve this goal. One example of its implementation in education is the use of websites in science learning. This study aims to evaluate the effectiveness of learning websites in improving student achievement. Method: Using the systematic literature review method, the research collects and analyzes twenty articles related to learning websites. Result: The results of the twenty journals showed that the use of website media has a positive impact on improving student achievement in the context of science learning. This reflects the critical role of technology in education in the era of global society 5.0. There has been a significant increase in minimum score achievement and student satisfaction with learning. Using the website allows students to learn efficiently and flexibly anywhere. This indicates that learning websites effectively aid students' comprehension of the material, motivate them to learn, and foster interest in learning. Novelty: The website learning media must continue to be developed. In the era of a global society, 5.0 technology in education is essential. This is based on an analysis of the data obtained regarding the use of website media for science learning.